The Effect of Using Skimming Technique on Students’ Reading Comprehension at SMAN 2 Karimun - Windasari, Windasari; Gushendra, Rizky (State Islamic University of Sultan Syarif Kasim Riau, 2023)
This research was conducted to know the average score of students‟ reading comprehensio before and after being taught by using Skimming Technique and to examine whether there is a significant effect of Skimming Technique on students‟ reading comprehension. This research was a pre-experimental design with quantitative approach. The population of the research was students of the eleventh grade at SMAN 2 Karimun. By having purposive sampling, the sample was class XI IPS 4 with a total of 30 students. The researcher used reading test in collecting the data. In data analysis, the researcher used non-parametric test. However, the data were interpreted by using Wilcoxon on the SPSS version 26.0 program. The result showed that the mean score of the students after being taught by using Skimming Technique (80.17) was higher than before being taught by using Skimming Technique (53.83). In conclusion, the use of Skimming Technique shows a significant effect on the students' reading comprehension at SMAN 2 Karimun.